2019
DOI: 10.1371/journal.pcbi.1006577
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based modeling of morphogenetic systems: Advantages and challenges

Abstract: The complexity of morphogenesis poses a fundamental challenge to understanding the mechanisms governing the formation of biological patterns and structures. Over the past century, numerous processes have been identified as critically contributing to morphogenetic events, but the interplay between the various components and aspects of pattern formation have been much harder to grasp. The combination of traditional biology with mathematical and computational methods has had a profound effect on our current under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 150 publications
(123 reference statements)
0
59
0
2
Order By: Relevance
“…Pattern formation is an essential feature of multicellular organism development, and variations in patterning mechanisms are thought to contribute substantially to morphological diversification. Consequently, pattern formation has fascinated scientists for centuries and, owing to its amenability to abstraction, has stimulated collaborations between experimental and theoretical biologists . Formation of periodic patterns, in particular, has attracted mathematicians and computational modelers alike .…”
Section: The Formation Of Repetitive Patterns In Nature—positional Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Pattern formation is an essential feature of multicellular organism development, and variations in patterning mechanisms are thought to contribute substantially to morphological diversification. Consequently, pattern formation has fascinated scientists for centuries and, owing to its amenability to abstraction, has stimulated collaborations between experimental and theoretical biologists . Formation of periodic patterns, in particular, has attracted mathematicians and computational modelers alike .…”
Section: The Formation Of Repetitive Patterns In Nature—positional Inmentioning
confidence: 99%
“…Consequently, pattern formation has fascinated scientists for centuries and, owing to its amenability to abstraction, has stimulated collaborations between experimental and theoretical biologists. [14][15][16] Formation of periodic patterns, in particular, has attracted mathematicians and computational modelers alike. 17 Two of the most prominent conceptual frameworks in the field of pattern formation are certainly Wolpert's theory on positional information, and Alan Turing's "reaction-diffusion"-based mechanisms.…”
Section: The Formation Of Repetitive Patterns In Nature-positional mentioning
confidence: 99%
“…An extensive review of cell-based models for general tissue mechanics can be found in [7]. Additionally, there are several reviews dealing with prominent applications areas, such as tumour growth [16,17] and morphogenetic problems [18,19,20]. In [21] the authors compare five cell-based frameworks (cellular automata, cellular potts, CBM OS and Voronoi variants and vertex models) with respect to four common biological problems: cell sorting, monoclonal conversion, lateral inihibition and morphogen-dependent proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…; Glen et al. ). These models give rise to different morphologies because they start from different initial conditions and include different networks of interactions between genes.…”
mentioning
confidence: 98%
“…Most mathematical models of development are based on similar interactions between gene products and cell behaviors (Oster and Alberch 1982;Raspopovic et al 2014;Osterfield et al 2017;Hirashima et al 2017;Glen et al 2019). These models give rise to different morphologies because they start from different initial conditions and include different networks of interactions between genes.…”
mentioning
confidence: 99%